Blender 3D : architecture, buildings, and scenery : create photorealistic 3D architectural visualizations of buildings, interiors, and environmental scenery /: architecture, buildings, and scenery : create photorealistic 3D architectural visualizations of buildings, interiors, and environmental scenery. (©2008) - Unknown
No abstract available